Paraguay : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2014 Article IV Consultation highlights that economic activity in Paraguay has slowed from record-high growth in 2013, but remains buoyant. Construction, manufacturing, and services led the expansion in 2014, whereas electricity production declined, and re-exports suffered from weak growth in Brazil. Full-year growth is estimated to have slightly exceeded 4 percent. Real GDP is projected to remain close to 4 percent in 2015. Weak trading partner growth and lower export prices cloud the outlook, and agricultural production is projected to rise only marginally above the high level of 2014.